Experiential Learning and Job Satisfaction of Students in a Technological University in the Philippines - Montalbo, Agnes (Journal of Technical Education and Training, 2022)
Preparing our students for future work roles is a critical component of any work-based learning like the technical and vocational education and training (TVET) and cooperative education (COE) program. The supervisor’s role, the location and atmosphere of the training site, interpersonal relationships, and a variety of other factors all contribute to a student’s training program’s effectiveness. Using a mixed-method approach, this study aimed to examine 75 undergraduate students’ learning experiences, personal evaluations, and satisfaction in their skills training. A focus group discussion was conducted, and a researcher-made questionnaire was developed to assess the students’ perceived skills as well as the process, location, training materials, and supervision of the training site. Students had a positive workplace learning in terms of the COE procedure, the environment and accessibility of the site, their cognitive, behavioral, and social learning experiences, their attitude toward their supervisor and coordinator, and their evaluation of training, according to the findings. In the focus group discussion, participants discussed issues that arose during their workplace learning experiences such as time management, interpersonal conflict, accessibility of the training site, and the COE process. The findings suggest that the training institution can provide high-quality and satisfactory training programs for undergraduate students. Curriculum review and pre-service seminars were proposed as interventions.